UNDERWATER IMAGING - Anuar, Ayob; Aslina, Mohd Jainal; Zairun, Roslan; Azyli Syabil Qawiem, Semuli; Daniel, Henry; Zara Ueni, Mohamed Azaddin; Ke Jun, Lai; Mohamad Imranuddin Zulfikar, Ritahuddin; Nixander Petrus Jau, Nixon; Mohamad Tamizie, Abdullah Saberi
The purpose of integrating practices, training, fieldwork, execution of innovative and creative publication under GKF2134 Underwater Imaging (Electronic Arts & New Media major under Fine Arts Program) course is to give exposure and to demonstrate the proper way of SCUBA diving in using underwater imaging equipment such as digital photography and videography devices in capturing images of ocean life to be shared with public.